Ulagalantha Perumal Temple - The Chola’s Royal Code of a Historical Survey and Surveyors - Elanchezian, SAV; Rajaraja Chozhan, VE (International Journal of Computer Sciences and Engineering, 2025)
the historical periods of surveying have been accounted in literatures like Ardhasastra. Monotonously, whether North India or South India they speaks on hastha units to linear measurements. There were, however, especially in Tamilnadu indeed a specific measurements have had used to land survey those known by feet based. Opposite to this we have hastha oriented that is fore arm based scales used especially in structural field which were accounted in silpa and vastu sastras. Surveying land could be a usual one however surveying a whole country was obviously very rare and a prestigious one. Performing ashvameta yaga and surveying a country was considered as great royal proud then. Besides, rarely this was expressed in art by few Kings according to Tamilnadu. Such of these glorious achievements were celebrated in those days style with their prideful medium of art. The introduction of striding sculpture of Vishnu as a presiding deity specifically in Kanchipuram is the matter of interpretation to this effort. Therefore this research paper lenses a new unviewed a historical great event of the Pallavas and Cholas which was celebrated through religious art architecture seems ambiguous and double entendre.